Decoupling atmospheric and oceanic factors affecting aerosol loading over a cluster of mesoscale North Atlantic eddies. Issue 11 (9th June 2014) - Lehahn, Yoav; Koren, Ilan; Rudich, Yinon; Bidle, Kay D.; Trainic, Miri; Flores, Jorge Michel; Sharoni, Shlomit; Vardi, Assaf
Abstract Using shipboard and satellite measurements we explore the environmental factors affecting the number concentration of aerosols with diameter 100 < D < 1000 nm over a cluster of three mesoscale (~10–100 km) eddies in the North Atlantic. Strongest sensitivity to environmental conditions was found in the 400 < D < 1000 nm size range. In this size range particle concentrations were closely linked to the surface wind speed, indicating in situ production of sea spray aerosols by wind‐driven processes. Particle concentrations were also affected by mesoscale variability in oceanic conditions at the vicinity of an anticyclonic eddy. In addition, a distinct aerosol population possibly produced at a distance of ~1000–2000 km from the study area was identified. The results highlight the importance of oceanic and atmospheric mesoscale processes in determining the characteristics of aerosols over the marine environment.